Formulation and Physico-Chemical Standardization of Triple Viburnum Leaf Arista and its Antiulcer Potentials - Prabhu, K.; Karar, P.K.; Hemalatha, S.; Ponnudurai, K. (Asian Journal of Chemistry, 2012)
A Triple Viburnum arista by anaerobic fermentation process was prepared. The formulated arista was standardized by some physico-chemical methods to obtain consistent parameters. The ED50 value of arista was calculated by Committee for the Purpose of Control and Supervision of experiments on animals (CPCSEA) guidelines method in terms of mg of arista per kg body weight equivalent to evaluate arista for its antiulcer potential in wistar rats. Water immersion plus restraint stress induced ulcer model was selected to study or screen the antiulcer potentials of the formulation against its solvent control group. The arista showed a significant antiulcer effect when the status of biochemical parameters such as superoxide dismutase; catalase; lipid peroxidation; gastric wall mucus were estimated and compared with the gastric juice of a healthy animal. The results observed were statistically significant (p < 0.001).